PENINGKATAN KUALITAS SPERMATOZOA PADA PROSES PEMISAHAN SPERMATOZOA DENGAN SENTRIFUGASI GRADIEN DENSITAS PERCOLL MELALUI PEMBERIAN FOSFOLIPID - Rumende, Rooije R.H.; Kalim, Handono; Widodo, M Aris; Djati, Moch Sasmito (Jurnal Kedokteran Brawijaya, 2007)
The separation of X and Y spermatozoa can be conducted by using Percoll Gradient Density Centrifugation(SGDP) method. It is, easy, valid, cheap and applicable method for developing made-insemination. Although it  has often been applied in sexing the spermatozoa, it was reported  that the method had often caused damages on the spermatozoa membranes and resulted in decreasing of the spermatozoa quality. The damages of spermatozoa after SGDP  process were specifically caused by (I) the loss of seminalplasma, (II) the increase of free radicals, and (III) the collision or friction among the spermatozoa. Among the three causal factors above, the third or the physical factor is claimed to be the most important one. It was assumed that the first and the second factors can be overcome if the third one is avoided. The spermatozoa membranes consist of lipids, protein, carbohydrate, and some substances at a low rate. Thegeneral objectives of this research was to identify the influence of the phospholipids PC (Phosphatidylcholin)to spermatozoa in order to avoid the damages of the spermatozoa in the process of SGDP.